Implementation of Foreign Language Institution Management in Improving the Arabic and English Language Skills of Santri at Modern Pesantren Misbahul Ulum - Fajar Rizki; Syahrizal Syahrizal; Jumat Barus (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to determine the Implementation of Foreign Language Institute Management in Improving the Arabic and English Language Skills of Santri at Modern Misbahul Ulum Islamic Boarding School. The type of research used is qualitative with descriptive survey techniques. The data presentation is done using comparative analysis. The results showed that the implementation of foreign language institute management can improve the Arabic and English language skills of students. The successful implementation of foreign language institute management is one of the foreign language institute management that is created and has been carried out in misbahul ulum modern pesantren, namely providing vocabulary (mufradat / vocabulary), language changes, muhadatsah (conversation), making mufradat exams, inter-dormitory drama, making place name boards in each pesantren area and strengthening foreign languages. The research output produced through the management of foreign language institutions in improving the Arabic and English language skills of santri is to produce graduates who not only master religious knowledge, but also have superior foreign language skills.